Device-associated infection rates and bacterial resistance in six academic teaching hospitals of Iran: Findings from the International Nocosomial Infection Control Consortium (INICC). Issue 6 (November 2015) - Jahani-Sherafat, Somayeh; Razaghi, Maryam; Rosenthal, Victor D.; Tajeddin, Elahe; Seyedjavadi, Simasadat; Rashidan, Marjan; Alebouyeh, Masoud; Rostampour, Maryam; Haghi, Arezo; Sayarbayat, Masoumeh; Farazmandian, Somayeh; Yarmohammadi, Tahere; et al.
Summary Device-associated health care-acquired infections (DA-HAIs) pose a threat to patient safety, particularly in the intensive care unit (ICU). However, few data regarding DA-HAI rates and their associated bacterial resistance in ICUs from Iran are available. A DA-HAI surveillance study was conducted in six adult and pediatric ICUs in academic teaching hospitals in Tehran using CDC/NHSN definitions. We collected prospective data regarding device use, DA-HAI rates, and lengths of stay from 2584 patients, 16, 796 bed-days from one adult ICU, and bacterial profiles and bacterial resistance from six ICUs. Among the DA-HAIs, there were 5.84 central line-associated bloodstream infections (CLABs) per 1000 central line-days, 7.88 ventilator-associated pneumonias (VAPs) per 1000 mechanical ventilator-days and 8.99 catheter-associated urinary tract infections (CAUTIs) per 1000 urinary catheter-days. The device utilization ratios were 0.44 for central lines, 0.42 for mechanical ventilators and 1.0 for urinary catheters. The device utilization ratios of mechanical ventilators and urinary catheters were higher than those reported in the ICUs of the INICC and the CDC's NHSN reports, but central line use was lower. The DA-HAI rates in this study were higher than the CDC's NHSN report. However, compared with the INICC report, the VAP rate in our study was lower, while the CLAB rate was similar and the CAUTI rate was higher. Nearly 83% of the samples showed a mixed-type infection. The most frequent pathogens were Acinetobacter baumannii, Staphylococcus aureus and Pseudomonas aeruginosa, followed by Klebsiella pneumoniae and Enterococcus spp. In the S. aureus isolates, 100% were resistant to oxacillin. Overall resistances of A. baumannii and K. pneumonia to imipenem were 70.5% and 76.7%, respectively. A multiple drug resistance phenotype was detected in 68.15% of the isolates. The DA-HAI rates in Iran were shown to be higher than the CDC-NHSN rates and similar to the INICC rates. Resistance to oxacillin and imipenem was higher as well. Comparing device use, DA-HAI rates, and bacterial resistance for the primary isolated bacteria indicated a direct association between urinary catheter use and the rates of CAUTI.